ANALISIS LIKUIDITAS, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agustin, Diah Rosalinda; Wahyuni, Ika; Widaninggar, Nanda (Fakultas Ekonomi dan Bisnis, 2024)
Companies with good performance will continue to experience good growth in the future. This research aims to analyze the influence of Liquidity, Profitability, Capital Structure on Share Prices and Company Value. Liquidity is measured using the Current Ratio, Profitability is measured using Return on Assets (ROA), and Capital Structure is measured using the Debit To Equity Ratio (DER). Share Prices are measured based on the Closing Share Price, while Company Value is measured using the Price To Book Value (PBV) Ratio. The data used is secondary data obtained from the financial reports of companies listed on the Indonesia Stock Exchange (BEI) during the 2020-2023 period. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Liquidity has a positive but not significant effect on Stock Prices, Profitability has a positive but not significant effect on Company Value, Capital Structure has a positive but not significant effect on Stock Prices, while Liquidity has a positive but not significant effect. significant effect on Company Value, Profitability has a positive but not significant effect and Capital Structure has a negatif but significant effect on Company Value. The results of the indirect influence hypothesis test show that liquidity has a negatif effect on Company Value through Share Prices, Profitability has a negatif but not significant effect on Company Value through share prices and capital structure has a negatif effect on Company Value through Share Prices.